PENGARUH PENERAPAN MODEL PEMBELAJARAN AUDITORY, INTELLECTUALLY AND REPETITION TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS IX SMPN 12 PADANG - Putri, Rozi Dwi (Jurnal Edukasi dan Penelitian Matematika, 2024)
Learners' ability to solve problems is an important skill that cannot be separated from learners. Initial test results at SMPN 12 Padang showed the need to improve this ability. One of the steps taken is the implementation of the Auditory, Intellectually and Repetition learning model. The results of the final test analysis of mathematical problem solving ability with a real level of α = 0.05, obtained a P-Value = 0.01 where the P-Value <α so as to reject  This means that the application of the Auditory, Intellectually and Repetition model has an impact on the mathematical problem solving ability of students in class IX SMPN 12 Padang.Keywords — Mathematical problem solving skill, Auditory, Intellectually and Repetition Learning Model